2020
DOI: 10.1039/d0py00087f
|View full text |Cite
|
Sign up to set email alerts
|

Bio-orthogonal triazolinedione (TAD) crosslinked protein nanocapsules affect protein adsorption and cell interaction

Abstract: Albumin-based protein nanocarriers obtained by TAD click chemistry have been widely exploited as drug delivery systems, since they show excellent degradability, low toxicity, but at the same time provide high loading capacity and relevant uptake into cells.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
9
0
2

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 11 publications
(11 citation statements)
references
References 48 publications
0
9
0
2
Order By: Relevance
“…This class of delivery vehicle provides excellent structural stability and a high degree of biodegradability, which can be exploited to control the release of payload. 21,22 The hollow nanocapsules are composed of crosslinked biopolymers and have a high loading capacity in their inner aqueous core. 23 They are highly degradable by intracellular proteinases under natural conditions but preserve their structural integrity in biological media during their delivery to the site of action.…”
Section: Introductionmentioning
confidence: 99%
“…This class of delivery vehicle provides excellent structural stability and a high degree of biodegradability, which can be exploited to control the release of payload. 21,22 The hollow nanocapsules are composed of crosslinked biopolymers and have a high loading capacity in their inner aqueous core. 23 They are highly degradable by intracellular proteinases under natural conditions but preserve their structural integrity in biological media during their delivery to the site of action.…”
Section: Introductionmentioning
confidence: 99%
“…In a similar approach, protein nanocarriers were formed via a Diels-Alder reaction of the tryptophan moieties of proteins with triazolinedione (TAD) in an inverse miniemulsion. [97] In this paper, the authors found that different crosslinking chemistries affected the protein conformation and hence carrierprotein and carrier-cell interaction. Other encapsulation strategies via inverse miniemulsion include carbohydrates as carrier Reproduced with permission.…”
Section: Nanocarriers By Chemical Reactionsmentioning
confidence: 95%
“…In a similar approach, protein nanocarriers were formed via a Diels‐Alder reaction of the tryptophan moieties of proteins with triazolinedione (TAD) in an inverse miniemulsion. [ 97 ] In this paper, the authors found that different crosslinking chemistries affected the protein conformation and hence carrier–protein and carrier–cell interaction. Other encapsulation strategies via inverse miniemulsion include carbohydrates as carrier materials, where for example azide‐modified hyaluronic acid [ 85 ] was crosslinked through a copper‐free azide–alkyne click chemistry with hexanediol dipropionate and dextran‐based polyaldehydes through polycondensation with polyhydrazides to pH‐responsive hydrazones.…”
Section: Encapsulation Of Hydrophilic Cargo Moleculesmentioning
confidence: 99%
“…[3][4][5][6] Especially NCs made from proteins have many advantages, such as their biodegradability, high loading capacity with a combination of hydrophilic drugs and low toxicity. [7,8] Due to their size, nanocarriers (NCs) can permeate cells easily and therefore it is of great importance to elucidate how the uptake and the further fate of the nanocarrier in the cell occur. [9] Nanocarriers are usually processed along the endolysosomal pathway.…”
Section: Introductionmentioning
confidence: 99%